Asymmetric synthesis of biologically useful 3,4-disubstituted gamma-lactone (3,4-Db) - Cheong, CS; Park, YJA; Lee, SH; Im, DS; Jung, SH (GORDON BREACH PUBLISHING, TAYLOR & FRANCIS GROUP, 2000)
3, 4-Disubstituted gamma -lactones 9 and 10 were stereoselectively synthesized from 3,4-unsaturated aliphatic alcohol. The synthetic methods of homoallylic alcohol were discussed. Asymmetric dihydroxylation of the double bond was performed by Sharpless' method with (DHQD)(2)PHAL or (DHQ)(2)PHAL. The stereo-chemistry of the product was assigned. The (3R,4R)- and (3S,4S)-compounds were obtained with high enantiomeric excess.
Keywords: DIHYDROXYLATION; INHIBITION; ANALOGS